2022
DOI: 10.33019/progresif.v16i2.2509
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Drone: Aset Militer, Perangkat Penelitian dan Kedaulatan

Abstract: This article discusses the legal issue of using underwater drones according to international maritime law and Indonesian national law. This discussion is necessary considering the use of underwater drones that cross national borders, there is no specific regulation. Therefore, it is necessary to make special arrangements regarding the use of underwater missiles both in terms of attack, spying, and marine data collection so that foreign countries do not freely operate underwater drones in the territorial sea of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The discovery of a drone from China in South Sulawesi is the third time a drone belonging to China has been found for spying purposes (Kompas, 2015). Finally, based on the results of the investigation, it was found that the object that was considered a drone was not a drone but a sea glider aimed at finding data related to temperature and, salinity which could be used for mining activities, underwater drilling activities, military activities to determine safe hiding points for submarines because salinity and currents will affect the performance of sonar to detect submarines under the sea (Putra et al, 2022). There were also drones for spying purposes in the United States, which were seen over the South China Sea in 2020 (CNBC, 2020).…”
Section: Civil Rights Related To the Use Of Drones For Spying Purposesmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of a drone from China in South Sulawesi is the third time a drone belonging to China has been found for spying purposes (Kompas, 2015). Finally, based on the results of the investigation, it was found that the object that was considered a drone was not a drone but a sea glider aimed at finding data related to temperature and, salinity which could be used for mining activities, underwater drilling activities, military activities to determine safe hiding points for submarines because salinity and currents will affect the performance of sonar to detect submarines under the sea (Putra et al, 2022). There were also drones for spying purposes in the United States, which were seen over the South China Sea in 2020 (CNBC, 2020).…”
Section: Civil Rights Related To the Use Of Drones For Spying Purposesmentioning
confidence: 99%
“…The legal loophole in terms of regulating drones is due to legal delays in adapting to existing technological developments, as mandated in Article 36 Additional Protocol I to the 1997 Geneva Convention, which stipulates that the state has an obligation to regulate developing weapons technology and developing methods of war in the country. So, in this case, every country must make rules regarding drones used in military matters, including weapons and non-military activities (Putra et al, 2022). Drone regulations (Prayogi, 2017a).…”
Section: B Drone Regulation In International Lawmentioning
confidence: 99%